Treatment of brainstem metastases with gamma-knife radiosurgery - (:unkn) unknown (SPRINGER, 2013)
The aim was to investigate the efficacy and safety of gamma-knife stereotactic radiosurgery (SRS) for treating brainstem metastases. The cases of 44 patients who underwent SRS as treatment for 46 brainstem metastases were retrospectively evaluated. The median age was 57 years (range 42-82 years) and the median Karnofsky performance score (KPS) was 80 (range 60-90). The primary tumor was lung carcinoma in 28 cases, breast carcinoma in 7 cases, colon carcinoma in 3 cases, renal cell carcinoma in 3 cases, malignant melanoma in 1 case, and unknown origin in 2 cases. Of the 46 metastases, 30 were in the pons, 14 were in the mesencephalon, and 2 were in the medulla oblongata. The median volume of the 46 metastases was 0.6 cc (range 0.34-7.3 cc). The median marginal dose of radiation was 16 Gy (range 10-20 Gy). Twenty-three patients (52 %) received whole brain radiotherapy prior to SRS, and 6 (14 %) received this therapy after SRS. In the remaining 15 cases (34 %), SRS was applied as the only treatment. Recursive partitioning analysis, graded prognostic assessment, and basic score for brain metastases were used to predict survival time. Local control was achieved for all but two of the 46 metastases (96 %). The overall survival time after SRS was 8 months. Female gender, KPS > 70, mesencephalon tumor location, and response to treatment were associated with longer survival. Basic score for brain metastases class I and recursive partitioning analysis classification were associated with better prognosis. Peri-tumoral changes were detected radiologically at 2 (4 %) of the metastatic lesion sites but neither of these patients exhibited symptoms. Gamma-knife radiosurgery is effective for treating brainstem metastases without a higher risk for radiation necrosis.
Keywords: Brainstem metastases; Gamma-knife; Radiosurgery; STEREOTACTIC RADIOSURGERY; PROGNOSTIC-FACTORS; RADIATION-THERAPY; TUMORS; EXPERIENCE; SURVIVAL; INDEX